Analisis Kemampuan Berpikir Kritis Matematis Siswa SMK Pada Materi Barisan dan Deret - Kharisma, Eka Noviana (JURNAL REVIEW PEMBELAJARAN MATEMATIKA, 2018)
This study aims to analyze the critical thinking skills of students of the vocational high school in mathematics concept of sequence and series. The method used in this research is descriptive qualitative with limited subjects that are 3 students of the vocational high school in Bandung district with high, medium and low classification. The main instrument in this study is the researchers themselves, critical thinking mathematical skill tests and interview guidelines. Results of this study show that the critical thinking skill mathematically owned by vocational students in Bandung district is still relatively low, it is based on written tests and interview with students.